2019
DOI: 10.1002/pchj.309
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the forest in order and the trees in disorder: Environmental orderliness versus disorderliness affects the perceptual processing style

Abstract: People attend to the same event or object by using a global or local processing style across different environments. Different physical environmental conditions, such as orderliness and disorderliness, activate different psychological states and produce different kinds of outcomes. However, previous work has rarely examined whether individuals exposed to different orderly or disorderly environments attend to the “global” or the “local” differently. Thus, in the current study, we conducted three behavioral expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Furthermore, the explanation based on the available self-control resources could be used not only for the effect of environmental orderliness on self-control behaviors and creative thinking; it might also be used to explain other psychological and behavioral effects of environmental orderliness. For example, an orderly experience leads to global perceptual processing, whereas a disorderly experience leads to local perceptual processing (Li et al, 2019b ), which may be because order increases the available self-control resources and disorder reduces the available self-control resources. A previous study has shown that the available self-control resources do play important roles in perceptual processing (Bruyneel and Dewitte, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the explanation based on the available self-control resources could be used not only for the effect of environmental orderliness on self-control behaviors and creative thinking; it might also be used to explain other psychological and behavioral effects of environmental orderliness. For example, an orderly experience leads to global perceptual processing, whereas a disorderly experience leads to local perceptual processing (Li et al, 2019b ), which may be because order increases the available self-control resources and disorder reduces the available self-control resources. A previous study has shown that the available self-control resources do play important roles in perceptual processing (Bruyneel and Dewitte, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research should consider directly comparing the two dependent variables under the same paradigm. In addition, future research could explore whether other dependent variables, such as immoral and illegal behavior (Keizer et al, 2008 ) perceptual processing (Li et al, 2019b ), are also moderated by trait self-control. If this hypothesis of a moderating role is still supported, it will provide more reliable evidence, which supports the suggestion that available self-control resources are the key mechanisms behind the psychological and behavioral effects of environmental orderliness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation